Determinan kejadian stunting pada bayi usia 6 bulan di Kota Semarang - Mustikaningrum, Ardian Candra; Subagio, Hertanto W; Margawati, Ani (Department of Nutrition Science, Faculty of Medicine, Universitas Diponegoro, 2016)
Background: Stunting is an indicator of chronic nutrition problems. Districts with the highest prevalence of stunting is the District Gunungpati (16,93%), Mijen (13,75%), and Tembalang (10,11%). The prevalence of stunting are more difficult to overcome with increasing age there should be a study to determine the incidence of stunting the determinant.Objective: To identify determinants of stunting in infants aged 6 months in the city of Semarang.Methods: case-control study, composed of 91 infants stunting and 91 normal infants. The sample selection using purposive sampling. Determinants studied were low birth weight, exclusive breastfeeding, complementary feeding Giving early, the incidence of diarrhea, ISPA, the allocation of parenting time mother, maternal height, maternal education, family economic level, and head circumference. The research instrument with a questionnaire, digital baby scales, infantometer, and metline. Data were analyzed with the value of odds ratiosÂ and multiple logistic regression.Results:The proportion of stunting was 39.6% in male babies and 60.4% in girls. Result of bivariate are low birth weight, the incidence of diarrhea, ISPA, maternal education, and family economic level association with stunting, but result in multivariate determinant incidence of stunting is the family's economic level (OR = 5,39, 95% CI = 2,73; 10,63, p<0,001), the incidence of acute respiratory infection (OR = 2,29, 95% CI = 1,16; 4,51, p=0,016). The family's economic level, the incidence of acute respiratory infection, and the incident of diarrhea contribute to stunting by 30%..Conclusion: The main determinants of stunting in infants 6 months is theÂ familyâ€™seconomic level.